AS LITERATURAS ORAIS E MARGINALIZADAS - Nogueira, Carlos (Organon, 2007)
Oral / popular / traditional literatures show specific ways of adaptation to new contexts and stimulus. This text is about their capacity of reinvention and of use of new media (from the book to the CD-ROM), where they prove to be alive under new forms, in a constant process of dynamic transformation.